PENGARUH LATIHAN SHOOTING DENGAN MASSED PRACTICE TERHADAP KETEPATAN DAN KETELITIAN SHOOTING BOLA BASKET PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER BOLA BASKET SMA N 1 PASIR PENYU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in examining the mastery of shooting techniques of the students of SMA Negeri 1 Pasir Penyu is still missing. The aim of this research is to determine the effect of mass practice target practice on the accuracy and precision of shooting basketball. The population in this research was all male students who participated in extracurricular basketball using a total sampling technique of 11 students. This type of research uses a single-group pre-test-post-test design. From the results of this research, it can be concluded that the students taking extracurricular basketball have an average post-test result of 9.81, based on the normality test of LoMaks pretest of 0.129 < L table 0.249, and post-test LoMaks of 0.153 < L table 0.249 would be normal. based on the statistical analysis of the t-test, the different values obtained are 2.36 and produce a tcount of 6,941 and a ttable of 1,812. Means tcount > ttable. It can be concluded that mass practice target shooting (X) has an effect on shooting accuracy and accuracy (Y) in male basketball athletes participating in extracurricular basketball at SMA N 1 Pasir Penyu.Key Words: Shooting Training, Massed Practice, Basket Ball